Calcineurin‐inhibitor induced pain syndrome due to interaction with clarithromycin: A case report - Satoshi Inaba; Hisatoshi Okumura; Tatsuya Aoki; Atsushi Kawashima (Journal of General and Family Medicine)
Abstract Calcineurin inhibitor‐induced pain syndrome (CIPS) is a rare but serious condition characterized by severe lower leg pain, often associated with elevated tacrolimus (TAC) levels. We report the case of a 57‐year‐old woman with rheumatoid arthritis (RA) who developed CIPS following a drug interaction between TAC and clarithromycin (CAM), a common macrolide antibiotic. Discontinuation of TAC led to a rapid resolution of symptoms. This case highlights the importance of monitoring TAC levels and being cautious of drug interactions, especially in primary care settings, to prevent adverse events like CIPS.